Waterproof lead frame for semiconductor packaging and manufacturing method thereof

By combining modified graphene oxide and modified Elosite nanotubes with materials such as water-based epoxy resins to form waterproof coatings and coat them on the surface of the lead frame, the problem of insufficient waterproof performance of existing copper-based alloy lead frames is solved, and the waterproof performance and device stability are significantly improved.

CN119542141AActive Publication Date: 2025-02-28TAIZHOU DONGTIAN ELECTRONICS
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411464934.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-28
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing copper-based alloy lead frame is relatively weak in waterproof design and cannot effectively prevent moisture and moisture penetration, resulting in corrosion and insulation failure of internal electronic components, reducing the reliability of the packaging.

Method used

Modified graphene oxide and modified Elosite nanotubes are combined with materials such as water-based epoxy resins, and water-based epoxy resins are formed through ultrasonic dispersion and reaction, and applied to the surface of the lead frame to form a waterproof coating to enhance its waterproof performance.

Benefits of technology

It significantly improves the waterproof performance of the lead frame, prevents moisture penetration, protects internal electronic components, and ensures the long-term stability and reliability of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of lead frames, in particular to a waterproof lead frame for semiconductor packaging and a manufacturing method of the waterproof lead frame. The preparation method comprises the following steps: ultrasonically dispersing modified graphene oxide in deionized water, heating to 40-50 DEG C, adding modified halloysite nanotubes, uniformly mixing, adding waterborne epoxy resin, a curing agent, a leveling agent and a defoaming agent, and uniformly mixing to obtain the waterproof coating. Performing electrolytic degreasing, acid pickling and plasma cleaning on the lead frame in sequence to obtain a pretreated lead frame; and coating the surface of the pretreated lead frame with a waterproof coating, and curing to form a waterproof coating, thereby obtaining the waterproof lead frame. The waterproof lead frame prepared by the invention not only has excellent waterproof performance, but also has excellent corrosion resistance, and the service life of the lead frame can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lead frames, in particular to a waterproof lead frame for semiconductor packaging and a manufacturing method thereof. Background Art

[0002] As electronic products develop towards miniaturization, high integration and high performance, packaging technology is also constantly improving. The lead frame is used as a mechanical support carrier for semiconductor chips, and with the help of leads (bonding gold or copper wires), the lead ends of the internal circuits of the chip are electrically connected to the external leads through the inner leads, forming a key component of the electrical circuit. In semiconductor chip packaging, the lead frame mainly plays the role of stabilizing the chip, conducting signals, and dissipating the heat generated by the chip when it is working.

[0003] The materials of lead frames are generally copper-based alloys and iron-nickel alloys. Copper-based alloys are widely used in the manufacture of semiconductor lead frames due to their advantages such as high strength, high electrical conductivity, excellent thermal conductivity and low price. However, existing copper-based alloy lead frames are usually weak in waterproof design and fail to effectively prevent the penetration of water and moisture. This defect is particularly obvious in humid or extreme environments, which may cause corrosion of internal electronic components, insulation failure and other problems, thereby reducing the reliability of the entire package.

[0004] Therefore, we propose a waterproof lead frame for semiconductor packaging and a manufacturing method thereof. Summary of the invention

[0005] The object of the present invention is to provide a waterproof lead frame for semiconductor packaging and a manufacturing method thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for manufacturing a waterproof lead frame for semiconductor packaging, comprising the following steps: Step S1: ultrasonically dispersing the modified graphene oxide in deionized water, heating to 40-50° C., adding the modified halloysite nanotubes and mixing evenly, then adding the waterborne epoxy resin, curing agent, leveling agent and defoaming agent and mixing evenly to obtain a waterproof coating; Step S2: performing electrolytic degreasing, pickling, and plasma cleaning on the lead frame in sequence to obtain a pretreated lead frame; Step S3: coating a waterproof coating on the surface of the pretreated lead frame, and after curing, forming a waterproof coating to obtain a waterproof lead frame.

[0007] Furthermore, the anti-corrosion coating comprises the following components by weight: 60-80 parts of waterborne epoxy resin, 80-100 parts of deionized water, 3-5 parts of modified graphene oxide, 5-10 parts of modified halloysite nanotubes, 8-12 parts of curing agent, 0.1-0.3 parts of leveling agent, and 0.1-0.2 parts of defoaming agent.

[0008] Furthermore, the preparation method of the modified graphene oxide is as follows: Step (1): ultrasonically dispersing graphene oxide in N,N-dimethylformamide, adding triphenylphosphine and hydroquinone, heating to 100-120° C., adding castor oil triglycidyl ether, reacting for 10-12 hours, then adding n-octadecyl mercaptan and a photoinitiator and mixing evenly, irradiating with ultraviolet light, filtering, washing, and drying to obtain an intermediate; Step (2): ultrasonically disperse the intermediate in N,N-dimethylformamide, add diamino-terminated polydimethylsiloxane, adjust the pH to 6-8 with sodium hydroxide, react at 30-40° C. for 20-24 hours, filter, wash and dry to obtain modified graphene oxide.

[0009] Furthermore, in the step (1), the mass ratio of graphene oxide, N,N-dimethylformamide, triphenylphosphine, hydroquinone and castor oil triglycidyl ether is 1: (100-200): (0.03-0.05): (0.005-0.008): (8-12).

[0010] Furthermore, in the step (1), the mass ratio of castor oil triglycidyl ether, n-octadecyl mercaptan and photoinitiator is 1:(1.0-1.2):(0.1-0.3), and the photoinitiator is 2-hydroxy-2-methylpropiophenone.

[0011] Furthermore, the process conditions of the ultraviolet irradiation are: irradiation wavelength 360-400nm, irradiation time 30-50min, irradiation intensity 20-35mW / cm 2 .

[0012] Furthermore, in the step (2), the mass ratio of the intermediate, N,N-dimethylformamide and diamino-terminated polydimethylsiloxane is 1:(100-200):(2-4).

[0013] Furthermore, the preparation method of the modified halloysite nanotubes is as follows: Step A: uniformly mixing halloysite nanotubes and sodium hydroxide solution, ultrasonically treating at 40-50° C. for 1-2 hours, centrifuging, washing and drying to obtain alkali-treated halloysite nanotubes; stirring the alkali-treated halloysite nanotubes and benzotriazole ethanol solution for 44-48 hours, vacuum extracting for 1-2 hours, standing at normal pressure for 30-50 minutes, filtering, washing and drying to obtain supported halloysite nanotubes; Step B: Under nitrogen protection, polyvinyl pyrrolidone and anhydrous ethanol are mixed evenly, and then glycidyl methacrylate is added. After heating to 70-80° C., azobisisobutyronitrile is added, and the mixture is reacted for 8-10 hours. After washing and drying, polyglycidyl methacrylate is obtained. Step C: uniformly mix the supported halloysite nanotubes, anhydrous ethanol, deionized water and 3-aminopropyltrimethoxysilane, react at 70-80°C for 4-6 hours, filter, wash and dry to obtain the amino halloysite nanotubes; uniformly mix the amino halloysite nanotubes and poly(glycidyl methacrylate), add deionized water for ultrasonic dispersion, react at 40-50°C for 22-24 hours, filter, wash and dry to obtain the modified halloysite nanotubes.

[0014] Furthermore, in step A, the mass ratio of halloysite nanotubes to sodium hydroxide solution is 1:(15-20), and the concentration of the sodium hydroxide solution is 3-5 mol / L.

[0015] Furthermore, in the step A, the mass ratio of the alkali-treated halloysite nanotubes to the ethanol solution of benzotriazole is 1:(30-40), and the concentration of the ethanol solution of benzotriazole is 40 mg / mL.

[0016] Furthermore, in step B, the mass ratio of polyvinyl pyrrolidone, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile is 1:(50-60):(3-5):(0.05-0.10).

[0017] Furthermore, in step C, the mass ratio of supported halloysite nanotubes to anhydrous ethanol, deionized water, and 3-aminopropyltrimethoxysilane is 1:(15-20):(4-6):(1-2).

[0018] Furthermore, in step C, the mass ratio of the aminated halloysite nanotubes, poly(glycidyl methacrylate) and deionized water is 1:(2-3):(100-150).

[0019] Furthermore, in step S2, electrolytic degreasing: the degreasing solution includes the following components: 140-145 g / L sodium chloride, 35-40 g / L sodium hydroxide, 4-6 g / L sodium silicate, 2-3 g / L sodium thiosulfate; the process conditions are: current density of 0.5-1.0 A / dm, temperature of 60-70°C, and time of 20-30 min.

[0020] Furthermore, in step S2, pickling: the acid solution includes the following components: 6-10wt% sulfuric acid, 2-4wt% ascorbic acid, and the rest is water; the process conditions are: the pickling time is 10-20s.

[0021] Furthermore, in step S2, the process conditions of plasma cleaning are: power of 200-300w, vacuum degree of 80-100Pa, atmosphere of Ar-H2, and cleaning time of 30-60s.

[0022] Furthermore, the curing agent is isophorone diamine curing agent.

[0023] Furthermore, the waterproof coating has a thickness of 50-150 μm.

[0024] Furthermore, the curing process conditions are: first curing at room temperature for 2-4 hours, and then curing at 120-150° C. for 4-6 hours.

[0025] Compared with the prior art, the present invention has the following beneficial effects: 1. A waterproof lead frame for semiconductor packaging and a manufacturing method thereof of the present invention comprises the following steps: synthesizing poly(glycidyl methacrylate) (PGMA) by free radical polymerization of glycidyl methacrylate (GMA), which contains a large number of epoxy groups; halloysite nanotubes have a certain load capacity and can be used as a carrier for controlling the release of corrosion inhibitors in self-repairing coatings; the corrosion inhibitor benzotriazole is loaded by alkali etching of halloysite nanotubes (HNTs) to obtain loaded halloysite nanotubes; the loaded halloysite nanotubes are surface-modified by the hydrolysis of 3-aminopropyltrimethoxysilane to introduce amino groups; finally, the amino groups in the aminated halloysite nanotubes react with the epoxy groups in PGMA to obtain modified halloysite nanotubes, which not only improves the compatibility between the material and the waterborne epoxy resin matrix, but also the modified halloysite nanotubes and the waterborne epoxy matrix can be co-cured with a curing agent containing amino groups to form a cross-linked network, thereby enhancing the density of the coating and improving its anti-corrosion effect.

[0026] 2. A waterproof lead frame for semiconductor packaging and a method for making the same, wherein the carboxyl groups of graphene oxide react with the epoxy groups in castor oil triglycidyl ether to generate a ring-opening reaction, thereby introducing a double bond and a relatively long fatty acid chain structure, and then utilizing n-octadecyl mercaptan to react with the double bond to generate a thiol-ene click reaction, thereby grafting a hydrophobic alkyl chain, thereby enhancing the hydrophobicity of the material, effectively improving the waterproof performance of the package, and ensuring the long-term stability of the semiconductor device; Bis(NH2-PDMS-NH2) terminated with bis(amino) groups is a kind of organic silicon oxide polymer, which has good chemical stability, electrical insulation and weather resistance, and has high shear resistance. Due to its low surface tension, it has good hydrophobicity and good anti-penetration effect for corrosive anions. Bis(amino-terminated) poly(dimethylsiloxane) is used as a bridge, and the amino group at one end of its structure reacts with the epoxy group of graphene oxide to obtain modified graphene oxide. At the same time, the amino group at the other end of the bis(amino-terminated) poly(dimethylsiloxane) structure can also react with the remaining epoxy group in PGMA to form a stable chemical bond, which improves the compatibility and bonding strength between the materials and enhances the overall performance. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In this embodiment, the lead frame: material C19400 copper alloy, thickness 2mm, sourced from Shanghai Xinye Metal Products Co., Ltd.; graphene oxide: thickness 1-3nm, diameter 4-7μm, number of layers 2-5 layers, sourced from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; bisamino-terminated polydimethylsiloxane: sourced from Shanghai McLean Biochemical Technology Co., Ltd.; halloysite nanotubes: outer tube 10-50nm, inner diameter 5-20nm, length 0.5-3um, number of crystal layers 15-40, sourced from Angxing New Carbon Materials Changzhou Co., Ltd.; water-based epoxy resin: E51, epoxy equivalent 184-194g / ep, sourced from Shenzhen Yoshida Chemical Co., Ltd.; curing agent: isophorone diamine curing agent, sourced from Zhangjiagang Yarui Chemical Co., Ltd.; leveling agent: model is Keying KYC-615; defoaming agent: model is BYK-028.

[0029] In the following examples and comparative examples, 1 part is equal to 10 g.

[0030] Embodiment 1: A method for manufacturing a waterproof lead frame for semiconductor packaging, comprising the following processes: Step S1: ultrasonically disperse 3 parts of modified graphene oxide in 80 parts of deionized water, heat to 40° C., add 5 parts of modified halloysite nanotubes and mix evenly, then add 60 parts of waterborne epoxy resin, 8 parts of curing agent, 0.1 parts of leveling agent and 0.1 parts of defoaming agent and mix evenly to obtain a waterproof coating; Step S2: the lead frame is subjected to electrolytic degreasing (the degreasing solution includes the following components: 140 g / L sodium chloride, 35 g / L sodium hydroxide, 4 g / L sodium silicate, 2 g / L sodium thiosulfate; the process conditions are: current density is 0.5 A / dm, temperature is 60°C, and time is 20 min), pickling (the acid solution includes the following components: 6 wt% sulfuric acid, 2 wt% ascorbic acid, and the rest is water; the process conditions are: pickling time is 10 s), and plasma cleaning (power is 200 W, vacuum degree is 80 Pa, atmosphere is Ar-H2, and cleaning time is 30 s) in sequence to obtain a pretreated lead frame; Step S3: coating a waterproof coating on the surface of the pretreated lead frame, first curing at room temperature for 2 hours, and then curing at 120° C. for 4 hours to form a waterproof coating, thereby obtaining a waterproof lead frame; The preparation method of modified graphene oxide is as follows: Step (1): ultrasonically disperse 3 parts of graphene oxide in 300 parts of N,N-dimethylformamide, add 0.09 parts of triphenylphosphine and 0.015 parts of hydroquinone, heat to 100°C, add 24 parts of castor oil triglycidyl ether, react for 10 hours, then add 24 parts of n-octadecyl mercaptan and 2.4 parts of photoinitiator and mix well, and irradiate with ultraviolet light (irradiation wavelength 360nm, irradiation time 30min, irradiation intensity 20mW / cm 2 ), filtering, washing and drying to obtain an intermediate; Step (2): ultrasonically disperse 3 parts of the intermediate in 300 parts of N,N-dimethylformamide, add 6 parts of diamino-terminated polydimethylsiloxane, adjust the pH to 6 with sodium hydroxide, react at 30°C for 20 hours, filter, wash and dry to obtain modified graphene oxide; The preparation method of modified halloysite nanotubes is as follows: Step A: 5 parts of halloysite nanotubes and 75 parts of 3 mol / L sodium hydroxide solution are mixed evenly, ultrasonically treated at 40°C for 1 hour, centrifuged, washed, and dried to obtain alkali-treated halloysite nanotubes; 5 parts of alkali-treated halloysite nanotubes and 150 parts of 40 mg / mL benzotriazole ethanol solution are stirred for 44 hours, vacuum extracted for 1 hour, and allowed to stand at normal pressure for 30 minutes, filtered, washed, and dried to obtain supported halloysite nanotubes; Step B: Under nitrogen protection, 4 parts of polyvinyl pyrrolidone and 200 parts of anhydrous ethanol were mixed evenly, and then 12 parts of glycidyl methacrylate were added. After heating to 70° C., 0.2 parts of azobisisobutyronitrile were added, and the mixture was reacted for 8 hours. After washing and drying, polyglycidyl methacrylate was obtained; Step C: Evenly mix 5 parts of supported halloysite nanotubes, 75 parts of anhydrous ethanol, 20 parts of deionized water and 5 parts of 3-aminopropyltrimethoxysilane, react at 70°C for 4 hours, filter, wash and dry to obtain amino-modified halloysite nanotubes; evenly mix 5 parts of aminated halloysite nanotubes and 10 parts of poly(glycidyl methacrylate), add 500 parts of deionized water for ultrasonic dispersion, react at 50°C for 24 hours, filter, wash and dry to obtain modified halloysite nanotubes.

[0031] Embodiment 2: A method for manufacturing a waterproof lead frame for semiconductor packaging, comprising the following processes: Step S1: ultrasonically disperse 4 parts of modified graphene oxide in 90 parts of deionized water, heat to 45° C., add 8 parts of modified halloysite nanotubes and mix evenly, then add 70 parts of waterborne epoxy resin, 10 parts of curing agent, 0.2 parts of leveling agent and 0.15 parts of defoaming agent and mix evenly to obtain a waterproof coating; Step S2: the lead frame is subjected to electrolytic degreasing (the degreasing solution includes the following components: 142 g / L sodium chloride, 38 g / L sodium hydroxide, 5 g / L sodium silicate, and 2.5 g / L sodium thiosulfate; the process conditions are: current density is 0.8 A / dm, temperature is 65°C, and time is 25 min), pickling (the acid solution includes the following components: 8 wt% sulfuric acid, 3 wt% ascorbic acid, and the rest is water; the process conditions are: pickling time is 15 s), and plasma cleaning (power is 250 W, vacuum degree is 90 Pa, atmosphere is Ar-H2, and cleaning time is 40 s) in sequence to obtain a pretreated lead frame; Step S3: coating a waterproof coating on the surface of the pretreated lead frame, first curing at room temperature for 3 hours, and then curing at 130° C. for 5 hours to form a waterproof coating, thereby obtaining a waterproof lead frame; The preparation method of modified graphene oxide is as follows: Step (1): ultrasonically disperse 4 parts of graphene oxide in 600 parts of N,N-dimethylformamide, add 0.16 parts of triphenylphosphine and 0.025 parts of hydroquinone, heat to 110°C, add 40 parts of castor oil triglycidyl ether, react for 11 hours, then add 44 parts of n-octadecyl mercaptan and 8 parts of photoinitiator and mix well, and irradiate with ultraviolet light (irradiation wavelength 380nm, irradiation time 40min, irradiation intensity 30mW / cm 2 ), filtering, washing and drying to obtain an intermediate; Step (2): ultrasonically disperse 4 parts of the intermediate in 600 parts of N,N-dimethylformamide, add 12 parts of diamino-terminated polydimethylsiloxane, adjust the pH to 7 with sodium hydroxide, react at 35°C for 22 hours, filter, wash and dry to obtain modified graphene oxide; The preparation method of modified halloysite nanotubes is as follows: Step A: 8 parts of halloysite nanotubes and 140 parts of 4 mol / L sodium hydroxide solution are mixed evenly, ultrasonically treated at 45° C. for 1.5 hours, centrifuged, washed, and dried to obtain alkali-treated halloysite nanotubes; 8 parts of alkali-treated halloysite nanotubes and 280 parts of 40 mg / mL benzotriazole ethanol solution are stirred for 46 hours, vacuum extracted for 1.5 hours, and allowed to stand at normal pressure for 40 minutes, filtered, washed, and dried to obtain supported halloysite nanotubes; Step B: Under nitrogen protection, 5 parts of polyvinyl pyrrolidone and 275 parts of anhydrous ethanol were mixed evenly, and then 20 parts of glycidyl methacrylate were added. After heating to 75° C., 0.4 parts of azobisisobutyronitrile were added, and the mixture was reacted for 9 hours. After washing and drying, polyglycidyl methacrylate was obtained; Step C: Evenly mix 8 parts of supported halloysite nanotubes, 140 parts of anhydrous ethanol, 40 parts of deionized water and 12 parts of 3-aminopropyltrimethoxysilane, react at 75°C for 5 hours, filter, wash and dry to obtain amino halloysite nanotubes; evenly mix 8 parts of aminated halloysite nanotubes and 20 parts of poly(glycidyl methacrylate), add 900 parts of deionized water for ultrasonic dispersion, react at 45°C for 23 hours, filter, wash and dry to obtain modified halloysite nanotubes.

[0032] Embodiment 3: A method for manufacturing a waterproof lead frame for semiconductor packaging, comprising the following processes: A method for manufacturing a waterproof lead frame for semiconductor packaging, comprising the following processes: Step S1: ultrasonically disperse 5 parts of modified graphene oxide in 100 parts of deionized water, heat to 50° C., add 10 parts of modified halloysite nanotubes and mix evenly, then add 80 parts of waterborne epoxy resin, 12 parts of curing agent, 0.3 parts of leveling agent and 0.2 parts of defoaming agent and mix evenly to obtain a waterproof coating; Step S2: the lead frame is subjected to electrolytic degreasing (the degreasing solution includes the following components: 145 g / L sodium chloride, 40 g / L sodium hydroxide, 6 g / L sodium silicate, 3 g / L sodium thiosulfate; the process conditions are: current density is 1.0 A / dm, temperature is 70°C, and time is 30 min), pickling (the acid solution includes the following components: 10 wt% sulfuric acid, 4 wt% ascorbic acid, and the rest is water; the process conditions are: pickling time is 20 s), and plasma cleaning (power is 300 W, vacuum degree is 100 Pa, atmosphere is Ar-H2, and cleaning time is 60 s) in sequence to obtain a pretreated lead frame; Step S3: coating a waterproof coating on the surface of the pretreated lead frame, first curing at room temperature for 4 hours, and then curing at 150° C. for 6 hours to form a waterproof coating, thereby obtaining a waterproof lead frame; The preparation method of modified graphene oxide is as follows: Step (1): ultrasonically disperse 5 parts of graphene oxide in 1000 parts of N,N-dimethylformamide, add 0.25 parts of triphenylphosphine and 0.04 parts of hydroquinone, heat to 120°C, add 60 parts of castor oil triglycidyl ether, react for 12 hours, then add 72 parts of n-octadecyl mercaptan and 18 parts of photoinitiator and mix well, and irradiate with ultraviolet light (irradiation wavelength 400nm, irradiation time 50min, irradiation intensity 35mW / cm 2 ), filtering, washing and drying to obtain an intermediate; Step (2): ultrasonically disperse 5 parts of the intermediate in 1000 parts of N,N-dimethylformamide, add 20 parts of diamino-terminated polydimethylsiloxane, adjust the pH to 8 with sodium hydroxide, react at 40°C for 24 hours, filter, wash and dry to obtain modified graphene oxide; The preparation method of modified halloysite nanotubes is as follows: Step A: 10 parts of halloysite nanotubes and 200 parts of 5 mol / L sodium hydroxide solution are mixed evenly, ultrasonically treated at 50° C. for 2 hours, centrifuged, washed, and dried to obtain alkali-treated halloysite nanotubes; 10 parts of alkali-treated halloysite nanotubes and 400 parts of 40 mg / mL benzotriazole ethanol solution are stirred for 48 hours, vacuum extracted for 2 hours, and allowed to stand at normal pressure for 50 minutes. After filtering, washing, and drying, supported halloysite nanotubes are obtained; Step B: Under nitrogen protection, 6 parts of polyvinyl pyrrolidone and 360 parts of anhydrous ethanol were mixed evenly, and then 30 parts of glycidyl methacrylate were added. After heating to 80° C., 0.6 parts of azobisisobutyronitrile were added, and the mixture was reacted for 10 hours. After washing and drying, polyglycidyl methacrylate was obtained. Step C: Evenly mix 10 parts of supported halloysite nanotubes, 200 parts of anhydrous ethanol, 60 parts of deionized water and 20 parts of 3-aminopropyltrimethoxysilane, react at 80°C for 6 hours, filter, wash and dry to obtain amino halloysite nanotubes; evenly mix 10 parts of aminated halloysite nanotubes and 30 parts of poly(glycidyl methacrylate), add 1500 parts of deionized water for ultrasonic dispersion, react at 50°C for 24 hours, filter, wash and dry to obtain modified halloysite nanotubes.

[0033] Comparative Example 1: A method for manufacturing a waterproof lead frame for semiconductor packaging, comprising the following processes: Compared with Example 2, in Comparative Example 1, the modified graphene oxide is replaced with graphene oxide of the same mass, and the other steps are the same as those of Example 2.

[0034] Comparative Example 2: A method for manufacturing a waterproof lead frame for semiconductor packaging, comprising the following processes: Compared with Example 2, in Comparative Example 2, the modified halloysite nanotubes are replaced with supported halloysite nanotubes of the same mass, and the other steps are the same as those of Example 2.

[0035] Comparative Example 3: A method for manufacturing a waterproof lead frame for semiconductor packaging, comprising the following processes: The preparation method of modified halloysite nanotubes is as follows: Step A: 8 parts of halloysite nanotubes and 140 parts of 4 mol / L sodium hydroxide solution are mixed evenly, ultrasonically treated at 45° C. for 1.5 hours, centrifuged, washed, and dried to obtain alkali-treated halloysite nanotubes; 8 parts of alkali-treated halloysite nanotubes and 280 parts of 40 mg / mL benzotriazole ethanol solution are stirred for 46 hours, vacuum extracted for 1.5 hours, and allowed to stand at normal pressure for 40 minutes, filtered, washed, and dried to obtain supported halloysite nanotubes; Step B: Under nitrogen protection, 5 parts of polyvinyl pyrrolidone and 275 parts of anhydrous ethanol were mixed evenly, and then 20 parts of glycidyl methacrylate were added. After heating to 75° C., 0.4 parts of azobisisobutyronitrile were added, and the mixture was reacted for 9 hours. After washing and drying, polyglycidyl methacrylate was obtained; Step C: 8 parts of supported halloysite nanotubes, 140 parts of anhydrous ethanol, 40 parts of deionized water and 12 parts of 3-aminopropyltrimethoxysilane are mixed evenly, reacted at 75°C for 5 hours, filtered, washed and dried to obtain amino-modified halloysite nanotubes; 8 parts of amino-modified halloysite nanotubes and 4 parts of poly(glycidyl methacrylate) are mixed evenly, 900 parts of deionized water are added for ultrasonic dispersion, reacted at 45°C for 23 hours, filtered, washed and dried to obtain modified halloysite nanotubes; Compared with Example 2, in step C of Comparative Example 3, the mass ratio of aminated halloysite nanotubes to poly(glycidyl methacrylate) is 1:0.5, and the other steps are the same as those in Example 2.

[0036] Experiment: The waterproof lead frames obtained in Examples 1-3 and Comparative Examples 1-3 were taken to prepare samples, and their performances were tested and the test results were recorded: The water contact angle was measured using a JC2000DM contact angle meter, and the volume of deionized water was 2 μL.

[0037] Coating salt spray resistance test: The sample size is φ10mm×2mm, and an “×” is drawn on the surface of the waterproof lead frame. Then, the sample is placed in a salt spray test chamber. Under the conditions of test temperature (35±2) ℃ and pH value 6.7-7.5, a 5% NaCl solution is used as the spray medium. The salt spray test is conducted for 720 hours, and a continuous spray method is used to analyze the salt spray aging performance.

[0038] Test Results

[0039] According to the data in the above table, we can clearly draw the following conclusions: Compared with Examples 1-3, the hydrophobicity and corrosion resistance of the products obtained in Comparative Examples 1 and 2 are both reduced, indicating that the modified graphene oxide prepared by the present invention has better hydrophobicity than graphene oxide; compared with the supported halloysite nanotubes, the modified halloysite nanotubes prepared by the present invention have better dispersibility and compatibility, thereby forming a more uniform composite material with the water-based epoxy resin matrix and the modified graphene oxide, thereby improving the waterproof and corrosion resistance of the material.

[0040] Compared with Examples 1-3, the hydrophobicity and corrosion resistance of the product obtained in Comparative Example 3 are both reduced. It can be seen that when the addition amount of poly(glycidyl methacrylate) is reduced, the reaction sites of epoxy groups on the surface of the modified halloysite nanotubes will be reduced, thereby affecting the performance of the waterproof coating.

[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for manufacturing a waterproof lead frame for semiconductor packaging, characterized in that: The steps include: Step S1: ultrasonically dispersing the modified graphene oxide in deionized water, heating to 40-50° C., adding the modified halloysite nanotubes and mixing evenly, then adding the waterborne epoxy resin, curing agent, leveling agent and defoaming agent and mixing evenly to obtain a waterproof coating; Step S2: performing electrolytic degreasing, pickling, and plasma cleaning on the lead frame in sequence to obtain a pretreated lead frame; Step S3: coating a waterproof coating on the surface of the pretreated lead frame, and after curing, forming a waterproof coating to obtain a waterproof lead frame.

2. The method for manufacturing a waterproof lead frame for semiconductor packaging according to claim 1, characterized in that: The anticorrosive coating comprises the following components by weight: 60-80 parts of waterborne epoxy resin, 80-100 parts of deionized water, 3-5 parts of modified graphene oxide, 5-10 parts of modified halloysite nanotubes, 8-12 parts of curing agent, 0.1-0.3 parts of leveling agent and 0.1-0.2 parts of defoaming agent.

3. The method for manufacturing a waterproof lead frame for semiconductor packaging according to claim 2, characterized in that: The preparation method of the modified graphene oxide is as follows: Step (1): ultrasonically dispersing graphene oxide in N,N-dimethylformamide, adding triphenylphosphine and hydroquinone, heating to 100-120° C., adding castor oil triglycidyl ether, reacting for 10-12 hours, then adding n-octadecyl mercaptan and a photoinitiator and mixing evenly, irradiating with ultraviolet light, filtering, washing, and drying to obtain an intermediate; Step (2): ultrasonically disperse the intermediate in N,N-dimethylformamide, add diamino-terminated polydimethylsiloxane, adjust the pH to 6-8 with sodium hydroxide, react at 30-40° C. for 20-24 hours, filter, wash and dry to obtain modified graphene oxide.

4. The method for manufacturing a waterproof lead frame for semiconductor packaging according to claim 3, characterized in that: In the step (1), the mass ratio of castor oil triglycidyl ether, n-octadecyl mercaptan and photoinitiator is 1:(1-2):(0.1-0.3), and the photoinitiator is 2-hydroxy-2-methylpropiophenone.

5. The method for manufacturing a waterproof lead frame for semiconductor packaging according to claim 3, characterized in that: In the step (2), the mass ratio of the intermediate, N,N-dimethylformamide and diamino-terminated polydimethylsiloxane is 1:(100-200):(2-4).

6. The method for manufacturing a waterproof lead frame for semiconductor packaging according to claim 2, characterized in that: The preparation method of the modified halloysite nanotubes is as follows: Step A: uniformly mixing halloysite nanotubes and sodium hydroxide solution, ultrasonically treating at 40-50° C. for 1-2 hours, centrifuging, washing and drying to obtain alkali-treated halloysite nanotubes; stirring the alkali-treated halloysite nanotubes and benzotriazole ethanol solution for 44-48 hours, vacuum extracting for 1-2 hours, standing at normal pressure for 30-50 minutes, filtering, washing and drying to obtain supported halloysite nanotubes; Step B: Under nitrogen protection, polyvinyl pyrrolidone and anhydrous ethanol are mixed evenly, and then glycidyl methacrylate is added. After heating to 70-80° C., azobisisobutyronitrile is added, and the mixture is reacted for 8-10 hours. After washing and drying, polyglycidyl methacrylate is obtained. Step C: uniformly mix the supported halloysite nanotubes, anhydrous ethanol, deionized water and 3-aminopropyltrimethoxysilane, react at 70-80°C for 4-6 hours, filter, wash and dry to obtain the amino halloysite nanotubes; uniformly mix the amino halloysite nanotubes and poly(glycidyl methacrylate), add deionized water for ultrasonic dispersion, react at 40-50°C for 22-24 hours, filter, wash and dry to obtain the modified halloysite nanotubes.

7. The method for manufacturing a waterproof lead frame for semiconductor packaging according to claim 6, characterized in that: In the step A, the mass ratio of the alkali-treated halloysite nanotubes to anhydrous ethanol, deionized water, and 3-aminopropyltrimethoxysilane is 1:(15-20):(4-6):(1-2).

8. The method for manufacturing a waterproof lead frame for semiconductor packaging according to claim 6, characterized in that: In the step C, the mass ratio of the aminated halloysite nanotubes, poly(glycidyl methacrylate) and deionized water is 1:(2-3):(100-150).

9. The method for manufacturing a waterproof lead frame for semiconductor packaging according to claim 2, characterized in that: The curing agent is isophorone diamine curing agent.

10. A waterproof lead frame for semiconductor packaging manufactured according to the manufacturing method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flame-retardant waterproof interior wall coating and preparation method thereof

    CN105820754A

  • Waterborne epoxy anti-corrosion paint containing graphene oxide and preparing method of waterborne epoxy anti-corrosion paint

    CN105838195A

  • Preparation method of silicate-mineral-modified reduced graphene oxide, application of silicate-mineral-modified reduced graphene oxide

    CN107266951A

  • Surface protection coating with seawater corrosion resistance and preparation method thereof

    CN108893031A

  • Anticorrosive and environmentally-friendly water-based coating and preparation method thereof

    CN109021788A